Profile of consumption of nutritional supplements for practitioners of physical exercise in the academies of the city of Vitória da Conquista -BA - Brito, Dirceu Santos (2012)
The objective of this study to check the consumption of nutritional supplements in physical exercise practitioners, aged between 18 and 60 years at gyms in Victory of Conquest -BA. It is a descriptive study. The sample consisted of 137 people; they are 46 users of nutritional supplements (47.5% males and 52.5% females). Consumption of nutritional supplements was determined by applying a questionnaire adapted bounded in the variables:most commonly used supplement, purpose of use, correct use, who said. The supplement most consumedwas thewhey protein (n = 11); Thermogenic (n = 11) andBCAA (n = 5);with daily consumption (52%). The main objective with supplementation wasthemuscle hypertrophy and 80% were satisfied with their use. The indication of the supplement was made in 33% of cases by the nutritionist. What was spent on nutritional supplements from R$51.00 to R$ 75.00 (31%). The time of exercise resulted in 3 to 6 hours / week (48%), 49% practice exercises to more than one year in order to increase muscle mass (50%) being the most practiced is the weight (39%). It was concluded that although it was higher prescription by a qualified professional, the use of supplements in the group studied is low, but it is always the need for nutrition education to ensure safe use.